Intercontinental dispersal prior to human translocation revealed in a cryptogenic invasive tree. - Hawkins, J; Boutaoui, N; Cheung, K; Klinken, v; Hughes, C (2007)
In this study, complementary species-level and intraspecific phylogenies were used to better circumscribe the original native range and history of translocation of the invasive tree Parkinsonia aculeata. Species-level phylogenies were reconstructed using three chloroplast gene regions, and amplified fragment length polymorphism (AFLP) markers were used to reconstruct the intraspecific phylogeny. Together, these phylogenies revealed the timescale of transcontinental lineage divergence and the likely source of recent introductions of the invasive. The sequence data showed that divergence between North American and Argentinean P. aculeata occurred at least 5.7 million years ago, refuting previous hypotheses of recent dispersal between North and South America. AFLP phylogenies revealed the most likely sources of naturalized populations. The AFLP data also identified putatively introgressed plants, underlining the importance of wide sampling of AFLPs and of comparison with uniparentally inherited marker data when investigating hybridizing groups. Although P. aculeata has generally been considered North American, these data show that the original native range of P. aculeata included South America; recent introductions to Africa and Australia are most likely to have occurred from South American populations.